PENGARUH PENGGUNAAN MEDIA BIG BOOK DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II SD NEGERI TEPUNG SARI - Nurahman, Riski; Hasim, Wahid (JS (JURNAL SEKOLAH), 2025)
Abstract: Early reading skills are an important foundation in the development of student literacy at the elementary school level. This study aims to analyze the effect of using Big Book media in improving the early reading skills of second-grade students at Tepung Sari Elementary School. The method used was an experiment with a nonequivalent control group design. The research sample consisted of 30 students, who were divided into two groups: experimental and control. Data collection techniques included observation, documentation, and tests. The results of the analysis using the independent sample t-test showed a significance value of 0.000 <0.05, which means there is a significant effect of using Big Book media on improving students' early reading skills. In addition, learning with Big Book media creates a more active and enjoyable learning atmosphere. Big Book media has been proven effective as a learning aid to improve elementary school students' early reading skills.  Keyword: Big Book, Early Reading, Learning Media, Elementary School Students Abstrak: Kemampuan membaca permulaan merupakan dasar penting dalam perkembangan literasi siswa di jenjang pendidikan dasar. Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan media Big Book dalam meningkatkan kemampuan membaca permulaan siswa kelas II SD Negeri Tepung Sari. Metode yang digunakan adalah eksperimen dengan desain nonequivalent control group design. Sampel penelitian berjumlah 30 siswa, yang dibagi menjadi dua kelompok: eksperimen dan kontrol. Teknik pengumpulan data meliputi observasi, dokumentasi, dan tes. Hasil analisis menggunakan uji independent sample t-test menunjukkan nilai signifikansi 0,000 < 0,05, yang berarti terdapat pengaruh signifikan dari penggunaan media Big Book terhadap peningkatan kemampuan membaca permulaan siswa. Selain itu, pembelajaran dengan media Big Book menciptakan suasana belajar yang lebih aktif dan menyenangkan. Media Big Book terbukti efektif sebagai alat bantu pembelajaran untuk meningkatkan keterampilan membaca permulaan siswa SD. Kata Kunci: Big Book, Membaca Permulaan, Media Pembelajaran, Siswa SD